Inspecting Edge Data Integrity With Aggregate Signature in Distributed Edge Computing Environment - Li, Bo; He, Qiang; Chen, Feifei; Jin, Hai; Xiang, Yang; Yang, Yun (IEEE transactions on cloud computing, 2022)
In the edge computing environment, app vendors can cache their data on a large number of geographically distributed edge servers to serve their users. However, those cached data are particularly vulnerable to both intentional and accidental corruption, which makes data security a major concern in the EC environment. Given limited computing resources of edge servers, how to effectively and efficiently inspect those data over tremendous edge servers is a critical and open problem. To tackle this edge data integrity (EDI) problem, we first study the entities, threats, system objectives, and the inspection mechanism, then propose a novel approach named EDI-S for inspecting the integrity of edge data and localizing the corrupted ones. Based on the elliptic curve cryptography, EDI-S generates one digital signature as the integrity proof for each replica. Then, multiple integrity proofs can be inspected altogether via an aggregate verification. This allows the integrity of tremendous cache data on multiple edge servers can be inspected more efficiently. EDI-S also provides two methods for localizing the corrupted data on edge servers, one for small-scale scenarios and the other for large-scale scenarios. Both theoretical analysis and experimentally evaluation demonstrate that EDI-S can solve the EDI problem effectively and efficiently.